Effect of Psychosocial Factors on Growth - Gohlke, Bettina C.; Bettendorf, Markus; Binder, Gerhard; Hauffa, Berthold; Reinehr, Thomas; Dörr, Helmuth-Günther; Wölfle, Joachim (Klinische Pädiatrie, 2021)
Background Genes, hormones and factors such as nutrition and psychosocial environment affect growth. Objective What is the significance of various psychosocial factors on growth? Methods Evaluation of results of a working meeting of paediatric endocrinologist with current literature research. Results Psychosocial deprivation in children can be associated with growth hormone deficiency (GHD) and short stature. GHD can be reversed by a change of environment and psychosocial support. War and migration are often associated with underweight, growth disturbances and poor health care. These factors can improve after the end of conflicts, but children often remain too short. Consumption of alcohol or opiates during pregnancy are associated with lower birth weight and increased risk of early and small for gestational age (SGA) childbirth. Children with attention deficit hyperactivity disorder show a slight slowdown in growth after they started stimulant therapy. However, they reach normal adult height. Conclusions In children with idiopathic short stature, psychosocial causes should be taken into account in the differential diagnosis. Notably there is an increased risk of growth disturbances in children from conflict regions or after prenatal drug exposure.
CRIS-Team WoS Importer:2021-12-24